Electrokinetic flow : characterization, control and application in microfluidic systems - Yan, Deguang (2008)
Advanced microfluidic devices can perform complete biochemical analysis in a single fabricated chip. One of the crucial issues in developing these microfluidic devices is to transport reagents and electrolytes to specified destinations without external intervention. The electrokinetic (EK) pumping can provide a kinetic source to route the liquid through microchannel networks. The EK pumping has numerous advantages including ease of fabrication, no need for moving parts, high reliability, and no noise, so that it has been extensively implemented in many microfluidic systems. The present study focuses on the characterization, control and manipulation of electrokinetic flows in microchannel network in order to optimally design and effectively control microfluidic devices. Specifically, due to strong relevance to the development of novel microfluidic devices such as milli-second capillary electrophoretic separation systems, AC pumps, advective chaotic micromixers etc., the time-dependent and frequency-dependent electroosmotic flows (EOF) are thoroughly investigated.